Coral forests diversity in the outer shelf of the south Sardinian continental margin. (April 2017) - Cau, Alessandro; Moccia, Davide; Follesa, Maria Cristina; Alvito, Andrea; Canese, Simonepietro; Angiolillo, Michela; Cuccu, Danila; Bo, Marzia; Cannas, Rita
Abstract: Ecological theory predicts that heterogeneous habitats allow more species to co-exist in a given area, but to date, knowledge on relationships between habitat heterogeneity and biodiversity of coral forests in the outer shelf and upper slope along continental margins is rather limited. We investigated biodiversity of coral forests from 8 sites spread over two different geomorphological settings (namely, pinnacles vs . canyons) in the outer shelf along Sardinian continental margin. Using a combination of multivariate statistical analyses, we show here that differences in the composition of coral assemblages among contrasting geomorphological settings were not statistically significant, whereas significant differences emerged among sites within similar geomorphologies (i.e. among pinnacles and among canyons). Our results reveal that environmental and bathymetric factors such as sediment coverage, slope of the substrate, terrain ruggedness, bathymetric positioning index and aspect were important drivers of the observed patterns of coral biodiversity, in both settings. Spatial variability of coral forests' biodiversity is affected by environmental factors that act at the scale of each geomorphological setting (i.e. within each pinnacle and canyon) rather than by the contrasting geomorphological settings themselves. This result allows us to suggest that simple categorization of benthic communities according topographically defined habitat is unlikely to be sufficient for addressing conservation purposes. Highlights: Coral communities dwelling on pinnacle or canyon did not show significant differences. The highest variability was observed among sites rather among contrasting areas. Bathymetric parameters do influence coral forests distribution within similar sites. Site-specific conservation measures should be preferred.